Bibliometric Review on Infrastructure Monitoring with IoT - Judijanto, Loso; Justam, Justam; Nampira, Ardi Azhar (Westscience Press, 2025)
The integration of the Internet of Things (IoT) into infrastructure monitoring has transformed how built environments are observed, maintained, and managed. This study conducts a comprehensive bibliometric review to map the research landscape, thematic trends, and collaboration patterns in the domain of IoT-based infrastructure monitoring. Using data retrieved from the Scopus database (2010–2024) and analyzed through VOSviewer, the study identifies key research clusters, influential authors, prolific countries, and the evolution of core topics over time. Results show that the research focus has shifted from basic sensor deployment and data acquisition to advanced topics such as machine learning, edge computing, data privacy, and cybersecurity. India, China, and the United States emerge as leading contributors, with dense global collaboration networks. The study highlights both the maturity of core research areas and the emergence of new directions such as blockchain integration and privacy-preserving infrastructure systems. These findings provide valuable insights for academics, policymakers, and practitioners aiming to enhance infrastructure resilience and efficiency through IoT technologies.